Reductive sequestration of Cr(VI) in soil and groundwater using Ca-Fe-S microparticles. Issue 2 (April 2023) - Wang, Jianle; Liu, Xueming; Deng, Hong; Zhao, Dongye; Yang, Qiulin; Zhu, Zhihua
Abstract: Various sulfur- and iron-bearing materials have been shown promising for reductive immobilization of Cr(VI) in water and soil. Yet, composite Ca-Fe-S materials and the effects of water chemistry and material aging have not been investigated. In this work, we prepared a type of Ca-Fe-S microparticles under the atmospheric conditions through a facile one-pot approach, and tested the particles for reductive immobilization of Cr(VI) in solution and soil. Ca-Fe-S showed 40 % higher removal efficiency of Cr(VI) in solution than FeSO4 and 10 % higher than CaSx on the basis of equal molar dosage. When a Cr-laden soil was amended by Ca-Fe-S, the leachable concentration of Cr per the toxicity characteristic leaching procedure remained below the regulatory limit of 5 mg L −1 after 730 days of curing, while FeSO4 and CaSx failed to meet the regulatory threshold. Ca-Fe-S served as a slow-releasing source of Fe 2+ and S 2-, which were able to convert Cr(VI) into the stable final product of Cr(OH)3 . Ca-Fe-S was able to perform well under a wide range of pH (3.0–9.0) and in the presence of high concentrations of coexisting ions (5 mmol L −1 of Cl -, SO4 2-, or HCO3 - ). Moreover, the material remained effective when aged under the atmospheric conditions for 14 days. This study showed that Ca-Fe-S is a highly effective material for efficient sequestration of Cr(VI) in soil and groundwater under various water chemistry and materials aging conditions. Graphical Abstract: ga1 Highlights: Ca-Fe-S microparticles were prepared and tested for immobilizing Cr(VI). Ca-Fe-S can rapidly immobilize Cr(VI) in soil and water over a pH range of 3.0–9.0. Ca-Fe-S was resistant to competition of co-solutes and oxidative aging/corrosion. Ca-Fe-S acted as a lasting source of Fe 2+ and S 2- that converted Cr(VI) into Cr(OH)3 . Immobilized Cr in soil remained stable after 730 days of aging under oxic conditions.